Cation hydration in hydrogelic polyacrylamide-phosphoric acid network: A study by Raman spectroscopy - Costa, A. M. Amorim da (2001)
The effects upon the structure and morphology of adding lithium, calcium and magnesium chlorides to a phosphoric acid/polyacrylamide 2:1 molar ratio proton conducting hydrogel are examined by observing the changes in the vibrational features of the polyacrylamide chain, in the phosphate group and in the interstitial water molecules as a function of the concentration and the cationic nature of the additive, at 295 K. On adding H3PO4 to the polyacrylamide hydrogel matrix, the amide groups become more accessible and the polyacrylamide-phosphoric acid network behaves like structure-makers promoting a larger association in the [`]bulk' liquid water molecules.